From periphery to consolidated city: strategies for the transformation of marginal urban zones (2005)
The article reveals the interest on the peripheral areas of contemporary cities, built during the years of the “residential expansionism”(central decades of the 20th century). To understand how these marginal areas have become central zones in the new territorial order, the article explores the periphery concept and its development during the 20th century, like a changing process. Then, the article explains the urban peripheries like a general phenomenon, evaluating some characteristics that appear in the same way in different urban cultures, like the European Mediterranean and the Latin American. Finally, the article identifies some characteristics of the process of urban transformation and “recualificación”, that begins after the last 25 years of the 20th century.